2017
DOI: 10.1515/zpch-2016-0961
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Raman Scattering of Nanoscale Silicon in Amorphous and Porous Silicon

Abstract: Abstract:The size effect of nanoscale silicon in both amorphous and porous silicon was investigated with micro-Raman spectroscopy. Silicon nanostructures in amorphous silicon were deposited on quartz substrates by plasma enhanced chemical vapor deposition (PECVD) with deposition powers of 15, 30 and 50 W. Micro-Raman spectra of the nanostructured silicon show the T

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 32 publications
2
22
0
2
Order By: Relevance
“…Typically, a sharp peak is observed at ∼520 cm −1 corresponding to crystalline Si and a broad peak centered around ∼480 cm −1 for amorphous Si. 35 For nanocrystalline Si, as the crystallite size and degree of crystallinity decrease, the peak shifts from 520 cm −1 to lower wavenumbers and the full width at half maximum (FWHM) of the peak increases. 36 While the powder XRD patterns of all the mp-Si NPs were similar, the Raman analysis revealed the differences in these samples (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Typically, a sharp peak is observed at ∼520 cm −1 corresponding to crystalline Si and a broad peak centered around ∼480 cm −1 for amorphous Si. 35 For nanocrystalline Si, as the crystallite size and degree of crystallinity decrease, the peak shifts from 520 cm −1 to lower wavenumbers and the full width at half maximum (FWHM) of the peak increases. 36 While the powder XRD patterns of all the mp-Si NPs were similar, the Raman analysis revealed the differences in these samples (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the Raman result confirms that no crystallization was observed on the HBP after heat treatment. For the USi_HBP and HSi_HBP electrodes, three characteristic broad peaks centered at 481 and 795 cm −1 were assigned to amorphous Si [ 31 , 32 , 33 , 34 ], whereas the D and G-bands of the CNT disappeared, indicating that the surface of the carbon electrode was covered by amorphous Si [ 34 ]. The Raman spectrum showed that the Si was still in the amorphous state, and a crystalline Si peak did not appear.…”
Section: Resultsmentioning
confidence: 99%
“…Сдвиг и появившуюся асимметрию главного пика мы связываем с возникновением нанокристалитов в этой области. Рассчитать размер нанокристаллитов можно по сдвигу ω фононной моды кремния [18]:…”
Section: результаты и обсужденияunclassified
“…Если происходит разупорядочение решетки, то полуширины полос КРС увеличиваются [11,12]. При уменьшении размеров кристаллов до размеров ∼ 2−10 nm происходит нарушение правил отбора по волновому вектору, и максимум полосы КРС смещается в сторону низких частот, а сама полоса становится асимметричной: появляется низкочастотное крыло основного колебания [13,14]. Из такого спектра по форме и положению линии КРС в области 520 cm −1 , отвечающей за колебания Si-Si, можно оценить размер нанокристаллов.…”
Section: Introductionunclassified